KORELASI KUALITAS HIDUP DAN FUNGSI KOGNITIF ANAK DOWN SYNDROME DI YPLB DEPOK - Hisanah, Lutfiyah Nadza; Mailani, Rena; Faradillah, Kiki Rezki; Oktarina1, Mona (Indonesian Journal of Physiotherapy, 2023)
ABSTRACT Background : Down syndrome cases in Indonesia will increase between 2010 and 2018. Down syndrome cases in Indonesia tend to increase.  In people with Down syndrome, chromosome number 21 does not split into two, but has three, or trisomy.  As a result, the baby has 47 chromosomes instead of the usual 46.  This causes abnormalities in the physical and mental development of children.This imperfect chromosome formation causes disturbances in cognitive function and quality of life during the child's growth phase. Methods : This study uses a correlational quantitative research design with a cross-sectional approach. With a sample of 83 children with Down Syndrome and with an error rate of 5%. This research was conducted offline using the cognitive scale for down syndrome (cs-ds) measurement tool and The TNO-AZL Questionnaire for Children's Health-Related Quality of Life (TacQol). Results : The results obtained in this study were that there was a significant relationship between cognitive function and quality of life in children with Down syndrome with a value of P = 0.000 for both variables and a correlation coefficient of r = 1.000 for cognitive function and r = 0.463 for quality of life. Because the value of r is positive for both variables, the relationship between the two variables is unidirectional. Conclusion : This study found that there is a relationship between cognitive function and quality of life in children with Down syndrome at YPLB Nusantara Depok.   Keywords: Down Syndrome; Quality of Life; CS-DS; TacQol; Physiotherapy